2014
DOI: 10.1007/s00784-014-1233-2
|View full text |Cite
|
Sign up to set email alerts
|

Fracture behavior of metal-ceramic fixed dental prostheses with frameworks from cast or a newly developed sintered cobalt-chromium alloy

Abstract: FDPs based on CAD/CAM milled and sintered frameworks may be an applicable and less technique-sensitive alternative to frameworks that are based on conventionally cast frameworks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 29 publications
3
58
0
2
Order By: Relevance
“…However, our study confirmed the result of a former study, which also showed almost no differences of retention forces in the range of 0° and 2° [24]. The similar trend of both fabrication methods, milling and casting Co-Cr alloy, has already been examined considering the fracture load of FDPs, showing no significant difference between milled and sintered and conventionally cast frameworks [7]. This trend seems to be in agreement to the retention forces measured in the present study and confirmed by the fact that the influence of taper angle exceeded the influence of the fabrication method [6].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, our study confirmed the result of a former study, which also showed almost no differences of retention forces in the range of 0° and 2° [24]. The similar trend of both fabrication methods, milling and casting Co-Cr alloy, has already been examined considering the fracture load of FDPs, showing no significant difference between milled and sintered and conventionally cast frameworks [7]. This trend seems to be in agreement to the retention forces measured in the present study and confirmed by the fact that the influence of taper angle exceeded the influence of the fabrication method [6].…”
Section: Discussionsupporting
confidence: 91%
“…One of these chalky blanks has already been examined in regard to the fracture behavior of fixed dental prostheses (FDPs). It emerged that the Sintron frameworks, being CAD/CAM milled and sintered, were comparable to conventional casted frameworks [7]. 15,17] and few complications [17], confirm the usage of Co-Cr alloy for RDPs.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The production of metallic restorations in the dental laboratory has conventionally been carried out using the traditional cast method based on the lost wax process [1,2,3]. Although the alloys of choice were gold-based when the casting technique was first developed, they were gradually replaced by base-metal alloys such as nickel-chromium (Ni-Cr) and cobalt-chromium (Co-Cr) alloys [2,4].…”
Section: Introductionmentioning
confidence: 99%